CONSTRUÇÕES GEOMÉTRICAS NA FORMAÇÃO DE PROFESSORES DE MATEMÁTICA NA UNIVERSIDADE FEDERAL DE MATO GROSSO DO SUL - MARIANA DUARTE DE SOUZA (2021)
Throughout this research, we went through two main objectives: to draw an overview of the disciplines that contemplate the geometric constructions in the Mathematics Degree courses at the Federal University of Mato Grosso do Sul (UFMS) and to problematize, based on the speech of our interlocutors, what are the contributions of these (s) for the training of mathematics teachers. We take Oral History as methodological support for our work, as it has been used in Mathematics Education. We analyzed the discipline of Geometric Constructions in all current courses in Mathematics at UFMS, aiming to understand how the historical emergence of this discipline was, who were the teachers who have taught it, how it is and was worked by them, what is the meaning given by teachers and students for this discipline for the training of mathematics teachers. This work is part of the project to map the training and practices of teachers who teach mathematics in Mato Grosso do Sul, from the HEMEP Group and the national equivalent developed by GHOEM. The various courses have in their grade a discipline equivalent to Geometric Constructions, practically with the same menu, however, some training courses for teachers of Mathematics at UFMS do not have it as mandatory. There is a tendency in the HEMEP Group to carry out historical and philosophical research involving Geometry, which we did through the bias of geometric constructions. As an analysis methodology, we chose to build open questions that would allow us to expand the dialogue, comparing our sources and literature. The questions elaborated were: 'Geometric Constructions: An elementary discipline?', 'Geometric Constructions: Change to improve?', 'Geometric Constructions: Adapt to survive?', 'Geometric Constructions: Fail to appreciate?' And 'Geometric Constructions: Which materials guide the teacher in conducting his discipline? '. In addition to these questions, a mapping of the Mathematics Degree courses with their respective years of creation was also made to better understand the context of these courses and their historical paths. We outline, based on the available deponents, the time frame in the research, from 2004 to 2019, which is the period in which the deponents in this research taught the discipline. We had as intentionality to discredit dogmatic discourses that touch the teaching of mathematics, such as the question of abandoning geometry. Among the final notes we highlight: the importance of these subjects in the sense of recovering contents of geometry that students should have studied in Basic Education; these subjects are often aimed at the substitute teacher; the absence of prior training to work in this discipline with a specific focus on teacher training. Didactic aspects such as failure and the use of computational technologies were also present.